Odlomek iz Jurčiča - Kmecl, Matjaž (Slavistična revija, 2008)
The article is an excerpt from a monograph about Jurčič as narrative prose writer and playwright. It critically illuminates two of his key stories, Hči mestnega sodnika and Sosedov sin. The author unearth the underlying paradigm of the former story and he is additionally critical towards the well-known opinions by criticism about the latter story. He considers it a typical example of a story like they were published in the series of Slovenske večernice.
Keywords: Jurčič, Josip, 1844-1881; kratka proza; povest; powest; realizem; Slovene literature; slovenska književnost